2017
DOI: 10.1111/sms.12825
|View full text |Cite
|
Sign up to set email alerts
|

Plasma volume reduction and hematological fluctuations in high‐level athletes after an increased training load

Abstract: The time course of plasma volume (PV) reduction following an increased training load period is unknown and was investigated. The accompanying fluctuations in [Hb] and OFF-hr score were analyzed in the Athlete Biological Passport. Further, whether fluctuations in plasma albumin, soluble transferrin receptors (sTfR), and pro-atrial natriuretic peptide (proANP) concentrations correlate with PV fluctuations was investigated. Eleven high-level competitive cyclists were investigated for 3 weeks. After initial measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…Similar to our findings, in a crossover design Keiser et al also implemented variable training loads set to elicit the same relative cardiac strain in both their hot and cool training conditions and also found that none of the heat adaptations (eg, increased PV) correlated to changes in exercise performance. Indeed, although not always shown, increased training load or multi‐day competition in already hypervolemic elite endurance athletes (international level cyclists) has been shown to augment PV by 5%‐20% in as little as 6‐7 days regardless of the heat load . Importantly, the current study's outcomes, in combination with training effects on PV, suggest that many of the previously published HA studies without an exercise control group in mild/cool conditions matched for relative cardiac work stress, may be showing outcomes that are due to both exercise stress, and metabolic heat.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Similar to our findings, in a crossover design Keiser et al also implemented variable training loads set to elicit the same relative cardiac strain in both their hot and cool training conditions and also found that none of the heat adaptations (eg, increased PV) correlated to changes in exercise performance. Indeed, although not always shown, increased training load or multi‐day competition in already hypervolemic elite endurance athletes (international level cyclists) has been shown to augment PV by 5%‐20% in as little as 6‐7 days regardless of the heat load . Importantly, the current study's outcomes, in combination with training effects on PV, suggest that many of the previously published HA studies without an exercise control group in mild/cool conditions matched for relative cardiac work stress, may be showing outcomes that are due to both exercise stress, and metabolic heat.…”
Section: Discussionmentioning
confidence: 50%
“…Indeed, although not always shown, 34 increased training load or multi-day competition in already hypervolemic elite endurance athletes (international level cyclists) has been shown to augment PV by 5%-20% in as little as 6-7 days regardless of the heat load. [35][36][37] Importantly, the current study's outcomes, in combination with training effects on PV, suggest that many of the previously published HA studies without an exercise control group in mild/cool conditions matched for relative cardiac work stress, may be showing outcomes that are due to both exercise stress, and metabolic heat. In our study, despite a 30% greater total AUC heat stress in the EUH and DEH groups, as well as a post-HA reduction in resting T c (a classic marker of HA) compared to CON, there was no further increase in PV or performance outcomes in the heat.…”
Section: Incorporation Of An Exercise Control Group At Same Relativmentioning
confidence: 65%
“…A number of possible factors may contribute to these extreme delta values, beyond the influence of altitude. First, training load or fatigue may be a factor, although this was controlled in most studies, athletes may still be tempted to train beyond their normal volumes in the performance testing setting . Further, hematological assessments performed on a rest‐day may influence the result .…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition to blood doping, several factors may affect the hematological profile, for example, altitude exposure, physical exercise, time of the day and year, and hydration status. [8][9][10][11][12] An increased knowledge of how these and other confounders interact with the hematological passport will further improve the interpretation of ABP results.…”
Section: Introductionmentioning
confidence: 99%